Pengaruh Penggunaan Media Story Stones terhadap Kemampuan Bahasa Ekspresif Lisan Anak Usia 4-5 Tahun di TK Gracia Sustain - Nia Devianna Laura Br Tarigan; Srinahyanti Srinahyanti (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Expressive language skills in children aged 4-5 years still face various problems that are not in accordance with their developmental stage, such as composing short sentences (children say "I draw a car" which should be the correct answer, namely "I want to draw a car"), expressing words clearly (saying "loti" which should be "roti") and also sometimes children speak ("i, eee, mama"), and this condition can certainly hinder the child's learning process at school. This research was conducted at Gracia Sustain Teladan Kindergarten Medan. This study aims to determine the effect of using story stones media on children's oral expressive language skills. The population in this study were all group A students at Gracia Sustain Teladan Kindergarten Medan in the 2025/2026 Academic Year. The type of research used in this study is a quantitative research method with a pre-experimental design in a one-group pretest-posttest design pattern. This research was conducted in 1 class using story stones media. The sample in this study used all members of the population as a sample with a total of 18 children. The statistical test results showed a significance value of 0.000 (p < 0.05), indicating that the use of story stones significantly impacted children's oral expressive language skills.